Risalah Fiqh Wanita Pemikiran Fiqh Perempuan Progresif KH. Muchith Muzadi - M.N. Harisudin (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2013)
This article examines KH Muchith Muzadi's thoughts on women's fiqh, known as progressive women's fiqh. In this treatise, KH Muchith Muzadi emphasizes the importance of a contextual approach in understanding Islamic law related to women, taking into account social dynamics, culture, and the needs of the times. Through an analysis of his works, this article identifies the basic principles underlying his progressive thinking, such as justice, equality and women's empowerment. In addition, the article also discusses the implications of these thoughts for the practice of fiqh in society, as well as the challenges faced in its implementation. Thus, this treatise is expected to make a significant contribution to women's fiqh discourse and encourage the reformation of thinking that is more inclusive and responsive to the needs of women in the contemporary era.